THE RELATIONSHIP BETWEEN MYOFILAMENT PACKING DENSITY AND SARCOMERE LENGTH IN FROG STRIATED MUSCLE - Brandt, Philip W. (The Rockefeller University Press, 1967)
In cross-sections of single fibers from the frog semitendinosus muscle the number of thick myofilaments per unit area (packing density) is a direct function of the sarcomere length. Our data, derived from electron microscopic studies, fit well with other data derived from in vivo, low-angle X-ray diffraction studies of whole semitendinosus muscles. The data are consistent with the assumption that the sarcomere of a fibril maintains a constant volume during changes in sarcomere length. The myofilament lattice, therefore, expands as the sarcomere shortens. Since the distance between adjacent myofilaments is an inverse square root function of sarcomere length, the interaction of the thick and the thin myofilaments during sarcomere shortening may occur over distances which increase 70 A or more. The "expanding-sarcomere, sliding-filament" model of sarcomere shortening is discussed in terms of the current concepts of muscle architecture and contraction.